Residual Waste of Boswellia Carterii Aromatic Oil Distillation as a Source of Natural Flavors - A. Gharb, Lamiaa (Al-Nahrain Journal of Science, 2025)
Nowadays, many researchers and industries prefer natural flavors over chemical ones. The main focus of the current research is to determine the flavoring compounds and terpenoids of by-products resulting from Boswellia carterii oleo-gum resin distillation, in addition to identifying active compounds in its essential oil. Aromatic oil was extracted from oleogum resin by using a Clevenger apparatus. In addition to the supernatant layer, which represents residual waste, was isolated by filtration. Both aromatic oil and residual waste were subjected to Gas chromatographic–mass spectral (GCMS) analysis. The results showed that B. carterii oil contains fourteen main active compounds, which include different terpenoid compounds. On the other hand, n-Octyl acetate (60.25%) represents the major components in this volatile oil. Residual waste analysis showed fifteen main active compounds, and the sesquiterpenoid compound 3,5,6,7,8,8a-Hexahydro-4,8a-dimethyl-6-(1-methylethenyl)-2(1H) naphthalenone was the major component with (17.23%) percent. The results indicated that both of essential oil and the upper layer of B. carterii (olibanum) residual waste were rich in valuable terpenoids and flavoring compounds, so waste could be used as an eco-friendly and natural source of these compounds with no cost.